Пародийное в романе Виктора Пелевина „Жизнь насекомых” - Nowakowska, Jana (Studia Rossica Posnaniensia, 2014)
Victor Pelevin’s The Life of Insects is an original modification of the novel as a genre in postmodern literature. The writer uses parody when he reduces the main characters to the level of insects. He combines realism and fantasy in a crooked, grotesque mirror. Ambiguous characters open up in fable-like situations and unmask not only the socially-determined people of Russia of the end of 20th century, but also universal patterns of human consciousness. Pelevin locates the world of people in the microcosmos of insects, thus foreshortening the perspective and changing the perception. This is an allegory of the very meaning of human existence.